The alpha 7, alpha 4 beta 2 and alpha 3 beta 4 Nicotinic Acetylcholine Receptors: Characteristics, Role in Pathogenic Processes and Bioactive Compounds - Batista, V. S. [UNESP]; Nascimento-Junior, N. R. [UNESP] (Brazilian Chemical Soc, 2016)
Neuronal nicotinic acetylcholine receptors (nAChRs) are potential targets for the treatement of several central nervous system disorders, including Alzheimer's disease, Parkinson's disease and schzophrenia. On this review will be discussed the main characteristics of the nAChRs, more specifically of the alpha 7, alpha 4 beta 2 and alpha 3 beta 4 subtypes, examples of bioactive compounds that act on these receptors and structureactivity relationships of some compounds on their respective target receptors.
Keywords: Medicinal chemistry; nicotinic acetylcholine receptors; bioactive compounds; structure-activity relationship